2020
DOI: 10.2147/ott.s252195
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA XIST Promotes Growth of Human Chordoma Cells by Regulating miR-124-3p/iASPP Pathway</p>

Abstract: Introduction: Chordoma is a malignant primary bone tumor that is found in the spine and skull. X-inactive specific transcript (XIST) is a long non-coding RNA (lncRNA) is known to be involved in the development of various cancers, but its precise function and mechanism in human chordoma have not been elucidated. Here, we investigated the role of lncRNA XIST in chordoma progression. Methods: Quantitative real time-polymerase chain reaction (qRT-PCR) was performed to determine lncRNA XIST expression in human chor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
(50 reference statements)
0
16
0
Order By: Relevance
“…One of the lncRNAs is the X-inactive-specific transcript (XIST), which can function as an oncogene or tumor suppressor gene in some types of cancer, including hepatocellular carcinoma, prostate cancer, and bladder cancer [ 57 , 58 ]. The mechanism by which lncRNA XISTs exert their effect involves an interaction with miRNA, acting as a molecule sponge to sequester miRNA and indirectly increase oncogene expression [ 59 ].…”
Section: Ar Signaling In Bladder Cancer Carcinogenesis: Initiation and Promotionmentioning
confidence: 99%
“…One of the lncRNAs is the X-inactive-specific transcript (XIST), which can function as an oncogene or tumor suppressor gene in some types of cancer, including hepatocellular carcinoma, prostate cancer, and bladder cancer [ 57 , 58 ]. The mechanism by which lncRNA XISTs exert their effect involves an interaction with miRNA, acting as a molecule sponge to sequester miRNA and indirectly increase oncogene expression [ 59 ].…”
Section: Ar Signaling In Bladder Cancer Carcinogenesis: Initiation and Promotionmentioning
confidence: 99%
“…The precise mechanism underlying the regulation of chordoma progression remains unknown. Increasing evidence has demonstrated that lncRNAs function as important regulatory molecules in tumor progression, including proliferation, invasion, migration and metastasis, and show dysregulated expression in chordoma tissues ( 7 , 12 15 ). Here, we identified a new chordoma regulator, lncRNA MDFIC-7, which was upregulated in tumor tissues of patients with chordoma.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al. demonstrated that lncRNA XIST plays a key role in chordoma progression by regulating the miR124-3p/iAPSS pathway ( 15 ), and Zhang et al. predicted the role of several lncRNAs in regulating dural penetration in clival chordoma through analyzing lncRNA and mRNA expression profiles ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SQ. Hai (2020) have indicated that LncRNA XIST/miR-124-3p/iASPP Pathway Promotes Growth of Human Chordoma Cells. Analogously, Lobo et al (2019) manifested that demethylated and methylated XIST promoter may be involved in testicular germ cell tumor development.…”
Section: The Role Of Lncrna Xist In Cancermentioning
confidence: 99%